Enhancing the National Spatial Data Infrastructure to Support 3D Real Estate Valuation: A Case Study of GIS-Supported Scoring of 3D Residential Units Based on Expert Opinion - Aydınoğlu, Arif Çağdaş; Bovkir, Rabia; Sisman, Suleyman; Kara, Abdullah (Wiley, 2025)
To support property valuation using three-dimensional (3D) real estate, the present study aims to extend the national spatial data infrastructure (NSDI) with value-affecting factors such as location characteristics, spatial planning, sociocultural information, and building and dwelling characteristics. To this end, the conceptual model proposed in ISO 19152-4 Land Administration Domain Model Part 4: Valuation information is first explored and integrated into the NSDI together with the local characteristics identified as necessary for 3D real estate valuations. The integrated model is then implemented and enriched with georeferenced 3D buildings and floor plans. A case study is then carried out in the city center, where the first 3D models of the building and residential units are produced. In the case study, an overall parametric value score is generated for each residential unit to support real estate valuation in conjunction with GIS analysis and relevant value-influencing factors as determined by a questionnaire completed by valuation experts, academics, and appraisers.
Keywords: 3D real estate valuation; GIS; LADM; NSDI; parametric value score